Optimization of the Meat Flavoring Production Process for Plant-Based Products Using the Taguchi Method - Varuzhan Sarkisyan; Anastasiya Bilyalova; Valentina Vorobyeva; Irina Vorobyeva; Alexey Malinkin; Vladimir Zotov; Alla Kochetkova (Foods)
The development of plant-based meat substitutes is imperative for reducing animal fat intake and promoting dietary diversification. However, the flavor profiles of these products frequently fall short of consumer expectations. This study sought to optimize the production process of meat flavorings for plant-based products using the Taguchi method. The study investigated the effects of sugar type, concentration, and reaction temperature on the Maillard reaction products, sensory characteristics, and volatile organic compounds. The thermal process flavors were obtained from the flavor precursor by heating in a laboratory microwave station at 30 bar for 15 min. The variable factors were the type of sugar (fructose, glucose, xylose), its concentration (25, 50, and 100 mM), and the temperature of the reaction (140, 150, and 160 °C). The study’s findings indicated that temperature emerged as the predominant factor influencing the formation of Maillard reaction products and the sensory characteristics of the flavorings. Specifically, 25 mM xylose-based flavorings prepared at 140 °C demonstrated the most notable meat flavor and the highest level of acceptability. Moreover, the analysis of volatile organic compounds revealed the presence of a diverse array of substances, including aldehydes, ketones, and alcohols, that are characteristic of meat flavor. A heat map of the volatile content was constructed to facilitate a comparison of the samples. The study demonstrates the effectiveness of the Taguchi method in optimizing the production process of meat flavorings for plant-based products and provides valuable insights for the development of more balanced odor profiles.